PRENATAL YOGA MENINGKATKAN KUALITAS TIDUR IBU HAMIL TRIMESTER III - Islah Wahyuni (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2022)
Sleep disorder is one of the uncomfortable by third trimester pregnant women. Sleep disorder include sleeplessness, subjective sleep disorder, poor sleep quality, lack of night's sleep, drowsiness that occurs during the day and awakens at night, the reported prevalence increased to 83.5% after the 8th gestational age month and can increase headaches, dizziness, lack of enthusiasm, activity and emotional disorder. The purpose of this study was to analyze the effect of prenatal yoga on the sleep quality of third trimester pregnant women. The research method used was a pre-experimental one group pre and post test with the Pittsburgh Sleep Quality Index (PSQI). The population of this study were third trimester pregnant women at PMB Islah Wahyuni with a sample of 11 people using consecutive sampling. Data were analyzed using paired t-test with SPSS. The results of this study were that the average PSIQ value of sleep quality for pregnant women before being given the prenatal yoga intervention was 23 points and after being given an average of 7.5 points. There was a difference in the PSIQ scores before and after being given the prenatal yoga treatment (p=0.000). Based on the results of the study, it is expected that mothers routinely practice prenatal yoga at home at least 2 times a week so that mothers still feel the effects of prenatal yoga for comfortable sleep until they enter labor.